2015
DOI: 10.1080/14786419.2015.1028059
|View full text |Cite
|
Sign up to set email alerts
|

In vitroantifungal activity of extracts obtained fromHypericum perforatumadventitious roots cultured in a mist bioreactor against planktonic cells and biofilm ofMalassezia furfur

Abstract: Xanthone-rich extracts from Hypericum perforatum root cultures grown in a Mist Bioreactor as antifungal agents against Malassezia furfur. Extracts of Hypericum perforatum roots grown in a bioreactor showed activity against planktonic cells and biofilm of Malassezia furfur. Dried biomass, obtained from roots grown under controlled conditions in a ROOTec mist bioreactor, has been extracted with solvents of increasing polarity (i.e. chloroform, ethyl acetate and methanol). The methanolic fraction was the richest … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
27
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 40 publications
(28 citation statements)
references
References 14 publications
1
27
0
Order By: Relevance
“…Extracts from its aerial parts are used internally for the treatment of depression, which affects more than 300 million people worldwide, and externally for the healing of skin disorders (W€ olfle et al, 2014;Apaydin et al, 2016;WHO, 2017). In addition, extracts from the roots are under study for their pronounced antifungal activity against human pathogens, including Candida species (Tocci et al, 2011(Tocci et al, , 2013aSimonetti et al, 2016). H. perforatum contains a number of bioactive constituents, which act additively and/or synergetically (Schmidt & Butterweck, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Extracts from its aerial parts are used internally for the treatment of depression, which affects more than 300 million people worldwide, and externally for the healing of skin disorders (W€ olfle et al, 2014;Apaydin et al, 2016;WHO, 2017). In addition, extracts from the roots are under study for their pronounced antifungal activity against human pathogens, including Candida species (Tocci et al, 2011(Tocci et al, , 2013aSimonetti et al, 2016). H. perforatum contains a number of bioactive constituents, which act additively and/or synergetically (Schmidt & Butterweck, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Antifungal susceptibility of M. furfur was determined according to standardized methods for yeast using the broth microdilution method with some modifications (CLSI M27‐A3, 2008; CLSI, ; Simonetti et al, ). Dermatophytes were grown on potato dextrose agar (Sigma Aldrich, St. Louis, Missouri, USA) at 28–30 °C until good conidial growth was present.…”
Section: Methodsmentioning
confidence: 99%
“…To overcome these drawbacks, special bioreactor setups were reported like gas phase or mist bioreactors. Simonetti et al [65] showed the possibility of cultivating SJW root cultures in mist bioreactors for 80 days. However, the authors focused mainly on the production of a special antifungal extract without detailed growth kinetics.…”
Section: Scale-up Potential In Bioreactormentioning
confidence: 99%